Passive stability characteristics of ankle braces and tape in simulated barefoot and shod conditions - Eils, E.; Imberge, S.; Völker, K.; Rosenbaum, D. (The American Journal of Sports Medicine, 2007)
Ankle sprains are among the most common injuries in barefoot sport activities such as dance, gymnastics, or trampoline. At present, the use of external ankle devices for prevention of ligament injuries for barefoot activities remains unclear.